Facile transmetallation of [SbIII(DOTA)]− renders it unsuitable for medical applications. Issue 10 (16th February 2022) - Chen, Catherine; Sommer, Charlotte; Thisgaard, Helge; McKee, Vickie; McKenzie, Christine J.
Abstract : The antimony(iii ) complex of 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetate (DOTA) has been prepared and its exceptionally low stability observed. Abstract : The antimony(iii ) complex of 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetate (DOTA) has been prepared and its exceptionally low stability observed. The Sb(iii ) ion in Na[Sb(DOTA)]·4H2 O shows an approximately square antiprismatic coordination geometry that is close to superimposable to the Bi(iii ) geometry in [Bi(DOTA)] − in two phases containing this anion, Na[Bi(DOTA)]·4H2 O, [H3 O][Bi(DOTA)]·H2 O for which structures are also described. Interestingly, DOTA itself in [(H6 DOTA)]Cl2 ·4H2 O·DMSO shows the same orientation of the N4 O4 metal binding cavity reflecting the limited flexibility of DOTA in an octadentate coordination mode. In 8-coordinate complexes it can however accommodate M(iii ) ions with r ion spanning a relatively wide range from 87 pm (Sc(iii )) to 117 pm (Bi(iii )). The larger Bi 3+ ion appears to be the best metal–ligand size match since [Bi(DOTA)] − is associated with greater complex stability. In the solution state, [Sb(DOTA)] − is extremely susceptible to transmetallation by trivalent ions (Sc(iii ), Y(iii ), Bi(iii )) and, significantly, even by biologically important divalent metal ions (Mg(ii ), Ca(ii ), Zn(ii )). In all cases just one equivalent is enough to displace most of the Sb(iii ). [Sb(DOTA)] − is resistant to hydrolysis; however, since biologically more abundant metal ions easily substitute the antimony, DOTA complexes will not be suitable for deployment for the delivery of the, so far unexploited, theranostic isotope pair 119 Sb and 117 Sb.